2004
DOI: 10.1079/bjn20041124
|View full text |Cite
|
Sign up to set email alerts
|

The use of glycaemic index tables to predict glycaemic index of composite breakfast meals

Abstract: The applicability of the glycaemic index (GI) in the context of mixed meals and diets is still debatable. The objective of the present study was to investigate the predictability of measured GI in composite breakfast meals when calculated from table values, and to develop prediction equations using meal components. Furthermore, we aimed to study the relationship between GI and insulinaemic index (II). The study was a randomised cross-over meal test including twenty-eight healthy young men. Thirteen breakfast m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
130
0
5

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(142 citation statements)
references
References 43 publications
7
130
0
5
Order By: Relevance
“…Although the product with 4 g of b-glucan had the lowest GI, it induced much greater insulinemia than the frozen product, which on the other hand had a higher GI. The inconsistency between GI and II is in line with previously published results (Flint et al, 2004).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Although the product with 4 g of b-glucan had the lowest GI, it induced much greater insulinemia than the frozen product, which on the other hand had a higher GI. The inconsistency between GI and II is in line with previously published results (Flint et al, 2004).…”
Section: Discussionsupporting
confidence: 91%
“…Insulin index (II) on the other hand, describes the effect that absorbed carbohydrates have on postprandial insulin levels (Juntunen et al, 2003). It has been generally accepted that there is a good correlation between GI and II of a product (Laville, 2004), but that is not always the case (Ostman et al, 2001;Flint et al, 2004). High-GI meals raise blood glucose levels quickly and stimulate insulin secretion.…”
Section: Introductionmentioning
confidence: 99%
“…A study by Wolever and Bolognesi (1996) suggested that GI determines the variability of the blood insulin response to a meal and the presence of protein and fat intake had negligible effects on postprandial glucose and insulin, while recently the opposite was reported by Flint et al (2004). A study investigating the effects of dietary GI and glycaemic load on energy metabolism and voluntary food intake in obese children showed that high-GI meals elicit a sequence of hormonal changes that might limit the availability of metabolic fuels and cause overeating in children (Ludwig et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Where no published data were available, published analogues were used (for example, the mean GI value for 'oranges' was imputed for 'clementines') or GI values were calculated from recipes using the mixed-meal formula 41 :…”
Section: Gi Calculationmentioning
confidence: 99%